FORECASTING AS A PRECONDITION FOR PLANNING IN SECURITY (Annual of the Faculty of Philosophy in Skopje, 2023)
Forecasting is an integral part of the planning process and analogously without forecasting we cannot even attempt to understand all the complexity of today’s world, the phenomena and processes that occur in it, the complexity of situations and systems if we do not face the need from their understanding and prediction. Analysing all aspects of forecasting is a very complex and difficult task, as it is characterized by great dynamism, complexity, and specificity. Therefore, the study of forecasting should primarily be based on its full understanding and differentiation from other security management functions to avoid any one-sidedness. Forecast within the framework of this paper primarily has several meanings. First, significant specifics and characteristics of the forecasting are determined. Second, in the context of forecasting, the emphasis is on forecasting and prognosing. Third, theoretical explication refers to establishing the causality of forecasting and planning in order to perceive the dialectical relationship and connection.
Keywords: forecasting; prognosing; assessment; planning; security functions